2019
DOI: 10.1111/clr.13440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enamel matrix derivative liquid in combination with a natural bone mineral on new bone formation in a rabbit GBR model

Abstract: Objectives:Recently, a new liquid carrier system for enamel matrix derivate (EMDliquid) was developed with better physico-chemical properties for improved adsorption of EMD to biomaterial surfaces. The aim of the present study was to investigate the bone regenerative potential of EMD-liquid in combination with a natural bone mineral (NBM) in vivo.Methods: Four 6-mm defects were created in the calvaria of six New Zealand white rabbits. Defects were filled with either (1) control (empty), (2) 20 mg of NBM, or (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In an in vitro study, Miron et al 33 found that EMD in a liquid type carrier with bone grafting materials showed higher absorption of amelogenin than the gel type counterpart if used with bone grafting materials. Several pre‐clinical studies evaluating bone formation capability of EMD in a liquid type carrier showed significantly greater new bone formation and less soft/connective tissue infiltration 32‐34 . These variations in EMD carrier may result in improvement of efficacy of EMD for the ARP procedure, but further research, including in vivo and clinical studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, Miron et al 33 found that EMD in a liquid type carrier with bone grafting materials showed higher absorption of amelogenin than the gel type counterpart if used with bone grafting materials. Several pre‐clinical studies evaluating bone formation capability of EMD in a liquid type carrier showed significantly greater new bone formation and less soft/connective tissue infiltration 32‐34 . These variations in EMD carrier may result in improvement of efficacy of EMD for the ARP procedure, but further research, including in vivo and clinical studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant increase in mineralized tissue was observed in white rabbits treated with NBM + EMD-liquid. 72 According to the results of a study published in 2019 by Lee et al it was also observed that the use of EMD in patients undergoing periodontal procedures greatly reduces the amount of pain and swelling felt and patients have a more comfortable post-operation period. 73 In addition to GFs that have been researched, there are GFs such as epidermal growth factor (EGF), insulin-like growth factor (IGF), stromal cell derived factor-1 (SDF-1), which have been less researched but have a positive effect on periodontal tissue regeneration.…”
Section: Biomolecule Delivery Biomaterials For Periodontal Regenerati...mentioning
confidence: 99%
“…86,87 Retrovirus, lentivirus, adenovirus, vaccinia virus, and adeno-associated virus (AAV) are examples of viral vectors. [88][89][90][91][92] Non-viral vectors have naked DNA which makes them easier to manufacture at low costs and insert into the cells. Gene delivery via non-viral vectors is called transfection.…”
Section: Reviewmentioning
confidence: 99%
“…Since the effects of amelogenins on cells involved in periodontal regeneration found substantial support in the literature, the hypothesis that EMD could stimulate osteoblast and bone regeneration has been studied both in recently published animal [ 8 , 9 ] and human studies [ 10 , 11 ]. Jung et al [ 9 ] compared the effect of EMD-liquid as an adjunct to biphasic calcium phosphate (BCP) in a rabbit calvarial model, as evaluated through micro-CT and histomorphometric analysis.…”
Section: Introductionmentioning
confidence: 99%